NEGATING STATES LOSSES APPROACH ON PUNISHMENT OF CORRUPTION - Fransiskus Arkadeus Ruwe (UNISSULA, 2018)
The criminal act of corruption is viewed from the formulation of the offense Article 2 of Act No. 31 Of 1999 concerning the Crime of Corrup tion is an economic offense caused by an act against the law, as a logical consequence of the Against the Law is to restore or negate the state's losses , achieve justice, utility and legal certainty, with priority on utility. Not becoming prevalent zero lo sses concept applied b ecause it is trapped in the prevalence of enforcing the law of corruption with the priority on legal certainty, it requires the progressive and militant spirit of the judges but a high and long commitment and a relatively long time to start with the target group within the judge t o get out of the routine of law enforcement that is running